Understanding and treating diabetic foot ulcers: Insights into the role of cutaneous microbiota and innovative therapies - Paul Norton; Pavlos Trus; Fengyi Wang; M. Julie Thornton; Chien‐Yi Chang (Wiley, 2024)
Abstract Background Notoriously known as the silent pandemic, chronic, non‐healing diabetic foot ulcers (DFUs), pose a significant rate of incidence for amputation and are a major cause of morbidity. Alarmingly, the treatment and management strategies of chronic wounds represent a significant economic and health burden as well as a momentous drain on resources with billions per annum being spent in the US and UK alone. Defective wound healing is a major pathophysiological condition which propagates an acute wound to a chronic wound, further propelled by underlying conditions such as diabetes and vascular complications which are more prevalent amongst the elderly. Chronic wounds are prone to infection, which can exacerbate the condition, occasionally resulting in amputation for the patient, despite the intervention of modern therapies. However, amputation can only yield a 5‐year survival rate for 50% of patients, highlighting the need for new treatments for chronic wounds. Findings The dynamic cutaneous microbiota is comprised of diverse microorganisms that often aid wound healing. Conversely, the chronic wound microbiome consists of a combination of common skin commensals such as Staphylococcus aureus and Staphylococcus epidermidis, as well as the opportunistic pathogen Pseudomonas aeruginosa. These bacteria have been identified as the most prevalent bacterial pathogens isolated from chronic wounds and contribute to prolific biofilm formation decreasing the efficiency of antimicrobials and further perpetuating a hyper‐inflammatory state. Discussion and Conclusion Here, we review recent advances and provide a new perspective on alternative treatments including phage and microbiome transplant therapies and how the definitive role of the cutaneous microbiota impacts the aetiology of DFUs.